Impact of Duration of Primary Education on School Outcomes: A Cross-Country Analysis - Luis Diaz-Serrano; Jessica Pérez (Institute for the Study of Labor (IZA), 2013)
Using panel data for non-OECD countries covering the period 1970-2012, this paper analyzes the impact of the duration of primary education on school enrollment, drop-outs and completion rates. The empirical results show that for children in elementary school one additional grade of primary education has a negative impact on enrollment rate, while the effect on drop-outs is positive. Analogously, we also observed that an additional grade in primary education reduces the enrollment rate in secondary education. These results are in line with the fertility model approach; that is, in developing and underdeveloped countries parents do not have incentive to send children to school given the high perceived present economic value of children.
Keywords: I21; I25; I28; 330; primary education; school achievement; political institutions; educational reforms